Dilated cardiomyopathy and progressive familial intrahepatic cholestasis. (20th March 2014) - James, Stephanie; Waterhouse, Deirdre; McDonald, Kenneth; O'Hanlon, Rory
Abstract : This case is of a 29-year-old man with progressive familial intrahepatic cholestasis type 1 also known as Byler's disease. At the age of 21, our patient developed non-ischaemic dilated cardiomyopathy. Cardiac MRI demonstrated global wall thinning, with significant areas of myocardial fibrosis in the mid and epicardial walls from base to apex on postgadolinium late contrast enhanced images. No shared genetic loci between dilated cardiomyopathy and Byler's or cholestatic liver disease have yet been found. This presents the first documented case of non-ischaemic dilated cardiomyopathy, with evidence of mid wall fibrosis, in association with an established diagnosis of progressive familial intrahepatic cholestasis type 1 since childhood.